Gender Differences in Affects and Craving in Alcohol‐Dependence: A Study During Alcohol Detoxification. (6th January 2017) - Petit, Géraldine; Luminet, Olivier; Cordovil de Sousa Uva, Mariana; Monhonval, Pauline; Leclercq, Sophie; Spilliaert, Quentin; Zammit, François; Maurage, Pierre; de Timary, Philippe
Abstract : Background: Alcohol craving is a major cause of relapse in alcohol‐dependent (AD) patients. It is closely related to the high depression and anxiety symptoms that are frequently observed at the early stages of abstinence, and these comorbid symptoms might thus constitute a relapse factor when they persist after detoxification. As these negative affects are known to evolve during the detoxification process, the aim of this study was to investigate the course of the relation between affects and craving during detoxification, with a particular attention given to gender in light of the known differences in affects between AD men and women. Methods: AD patients ( n = 256) undergoing a detoxification program were evaluated for positive (PA) and negative affectivity (NA), depression and anxiety symptoms, and craving, twice within a 3‐week interval (on the first [T1] and the eighteenth day [T2] of abstinence). Results: Detoxification course was associated with improvements regarding NA, depression and anxiety symptoms, and craving. Moreover, these negative affects were related to craving intensity. However, for men, the relation was only present at the beginning of detoxification, while, for women, it persisted at the end of detoxification as did high levels of depression. Furthermore, only with women was the level of craving at T2 proportional to negative affects reported at T1, and depression symptoms experienced at T1 were reliable predictors of craving at T2. Conclusions: Given the importance of craving in relapse, special care should be given to improve depressive symptoms in AD women to promote long‐term abstinence. Also, the remaining portion of AD women who still exhibit substantial symptoms of anxiety and depression at the end of detoxification could benefit from an integrated treatment simultaneously tackling mood and alcohol‐dependence disorders. Abstract : Alcohol detoxification is associated with improvements of depression symptoms and craving. Clear links exist between depression and craving intensity, but are gender dependent. For men, depression is essentially present at the beginning of detoxification (BOD), where it is related to craving. For women, severe depression symptoms are present in 60% at the BOD and persist at the end of detoxification (EOD) in 23%. At the EOD, craving is related to depression symptoms in women only.